‘It looks better than a bowl of mush’: Views on the use of food design strategies, including 3D food printing, to improve meals for people with dysphagia - Bronwyn Hemsley (International Journal of Food Design)
To improve meals for people with dysphagia, we explored the views of people with dysphagia, their supporters and allied health professionals on a range of food design strategies (e.g. food shaping and food presentation techniques), including 3D food printing. From November 2021 to February 2022, an online survey of (1) adults with dysphagia (n = 30) and (2) supporters of people with dysphagia and allied health professionals (n = 22) was conducted. The survey included multiple choice, Likert scale and open-ended questions. Data was analysed descriptively. Most participants across the two groups had used at least one food design strategy for texture-modified foods and none had used 3D food printing. People with dysphagia were less likely to use food shaping techniques in preparing their texture-modified meals than other respondents. Supporters of people with dysphagia and allied health professionals were more likely than people with dysphagia to use food shaping techniques and to consider that 3D food printing could improve the visual appeal and enjoyment of texture-modified foods. A range of issues impacting the feasibility of 3D food printing were identified. The use of food design strategies for texture-modified foods may increase the food choices and mealtime enjoyment of people with dysphagia. Further research exploring how people with dysphagia and their supporters engage with 3D food printing could identify further influences on their future use of these technologies.